Synthesis and crystal structure of a bench-stable pyridinium ketene hemiaminal: 1-(1-ethoxyethenyl)-2-[methyl(phenyl)amino]pyridin-1-ium trifluoromethanesulfonate - Zoe A. Krevlin; Isabella C. Bote; Maria Christina F. Crespo; Christie C. Lam; Colin D. McMillen; Max M. Majireck (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The novel bench-stable N-quaternized ketene N,O-acetal, C16H19N2O+·CF3O3S−, was synthesized and its structure determined. The title compound is a rare example of a pyridinium ketene hemiaminal for which a crystal structure has been determined, joining the 2-chloro-1-(1-ethyoxyethenyl)pyridin-1-ium trifluoromethanesulfonate salt from which it was synthesized. The cationic species of the title compound can be defined by three individually planar fragments assembling into a non-coplanar cation. The phenyl substituent extending from the amino nitrogen atom and the ethyoxyvinyl substituent extending from the pyridine N atom are oriented on the same side of the molecule and maintain the closest coplanar relationship of the three fragments. Supramolecular interactions are dominated by C—H...O interactions from the cation to the SO3 side of the trifluoromethanesulfonate anion, forming a two-dimensional substructure.